OC-069 Outcomes of endoscopic resection of complex colorectal lesions referred to a tertiary institution after failed attempts at resection or extensive manipulation. (17th June 2017) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: Substantial manipulation or sampling of large colorectal lesions prior to endoscopic resection can have significant effects on the feasibility and outcomes of endoscopic treatment. Failed attempts at resection and extensive sampling of lesions prior to referral to a specialist centre are common in western practice. However, there are few data defining the scope of the problem and the effects on outcomes following endoscopic resection. We examined the effect of significant prior manipulation on the feasibility and outcomes of endoscopic resection of complex colorectal neoplasms in a UK tertiary referral centre. Method: Patients who underwent endoscopic resection of colorectal lesions≥2 cm were included. Lesions were assessed with magnification chromoendoscopy supplemented by colonoscopic ultrasound. A lesion specific approach was used to decide on resection technique. Patients were grouped according to whether they had previous failed attempts at resection, heavy manipulation (≥6 biopsies or tattoo into the lesion), or minimal sampling only (<6 biopsies). Outcomes included initial successful endoscopic resection, complications, recurrence and the need for surgery. Results: Endoscopic resection was performed for 408 large colorectal lesions (EMR n=327, ESD n=43, hybrid procedures using ESD n=38). Mean lesion size was 55.6 mm +/-30.7 mm. 216 (53%) lesions had been subjected to failed attempts at resection or heavy manipulation prior to referral. In 92 lesions (23%), an average of 1.5 (range 1–6) previous attempts at resection had been made, including 54 attempts at transanal surgical resection in 21 cases. A further 124 lesions (30%) had been extensively sampled or tattooed. Initial endoscopic resection was deemed successful in 97% of cases after previous failed attempts, 96% of cases with prior heavy manipulation and 97% of other cases (p=0.68). En bloc resection was possible in fewer patients with previous attempts at resection (14%, 31% and 42% respectively, p<0.001). Complication rates were similar for patients with failed prior attempts at resection compared to other patients (4.4% versus 6.7%, p=0.42). Recurrence rates were 21.7%, 12.1% and 9.0% respectively (p=0.01). 89% of patients without invasive cancer who had prior failed attempts at resection were free from recurrence and had avoided surgery at last follow up compared to 98% of those after prior heavy manipulation and 96% of others (p=0.04). Conclusion: After failed attempts at resection, patients have lower en bloc resection rates and higher recurrence rates. Nevertheless, specialist management in a dedicated tertiary unit results in successful, organ preserving endoscopic treatment of these extremely challenging lesions in 89% of cases with low complication rates. Disclosure of Interest: None Declared